Effect of Traditional Chinese Medicine characteristic nursing combined with Liuzijue Qigong on rehabilitation of cardiac function in patients with chronic heart failure (中医特色护理联合六字诀对慢性心力衰竭患者心功能康复的影响) - HUANG Yingmei (黄颖梅); LI Qingling (李庆玲); CHEN Yao (陈瑶); CHEN Ying (陈颖); HONG Ming (洪明); YUAN Yuan (袁园) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the effect of Traditional Chinese Medicine (TCM)characteristic nursing combined with Liuzijue Qigong on rehabilitation of cardiac function in patients with chronic heart failure (CHF). Methods A total of 80 CHF patients were randomly divided into the study group and control group, with 40 cases in each group. All patients received routine drug therapy during hospitalization. Patients in the control group were give routine care including work-rest schedule, dietary guidance, psychological care and daily care. Patients in the study group were given TCM characteristic nursing combined with Liuzijue Qigong in addition to routine care. The Minnesota Living with Heart Failure Questionnaire (MLHFQ) was used to measure the patient quality of life, and outcomes of left ventricular ejection fractions (LVEF) and 6-minute walking test were measured and compared between two groups. Results Longer 6MWD and higher LEVF were reported in both groups at three months of intervention, and patients in the study group achieved better outcomes of 6MWD and higher LEVF compared with those in the control group(P＜0. 01). The score of MLHFQ decreased in both groups at three months of intervention, and score of MLHFQ in the study group was lower than that in the control group (P＜0. 01). Conclusion The TCM characteristic nursing combined with Liuzijue Qigong is potentially effective to improve the rehabilitation of cardiac function and long-term quality of life in CHF patients. (目的 探讨运用中医特色护理联合六字诀促进慢性心力衰竭患者心功能康复的效果。方法 选取2020年9月-2021年9月住院治疗的慢性心力衰竭患者80例为研究对象, 随机分为研究组和对照组, 各40例。两组患者均接受心力衰竭常规药物治疗。对照组采用常规护理, 指导患者休息与活动, 给予合理饮食指导、心理护理、生活护理等; 研究组在常规护理的基础上给予中医特色护理及气功六字诀指导。采用明尼苏达心力衰竭生活质量调查表(MLHFQ)评估患者生活质量, 记录左室射血分数(LVEF)和六分钟步行试验(6MWD)结果。结果 干预3个月时, 两组6MWD距离和LEVF均较入院时增加, 且研究组6MWD距离和LEVF较对照组改善明显, 差异有统计学意义(P＜0. 01)。干预3个月时, 两组MLHFQ评分均较入院时降低, 且研究组MLHFQ评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 中医特色护理联合六字诀能改善慢性心力衰竭患者的心功能, 减轻临床症状, 提高患者的远期生活质量。)